PENGIMPLEMENTASIAN KNOWLEDGE SHARING DALAM RUANG LINGKUP ORGANISASI MAHASISWA - Putri, Oktafiana; Daulay, Rosniar (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
Knowledge sharing is the organization's ability to increase knowledge effectively by creating, sharing and using previously applied knowledge. This article contains a collection of theories from experts complemented by the author's premise from several articles published abroad that have been reviewed by the author. And equipped with an analysis of one of the organizations that enforce knowledge sharing. Knowledge can be carried out when members of student organizations are holding meetings or regular meetings, so SECI models, especially tacit knowledge can be carried out, for explicit knowledge, it can be seen during the process of making and preparing the AD / ART book, where all knowledge about the organization comes from a book. Sharing knowledge is a way of maintaining and passing on the knowledge possessed by an individual, organization or society about something so that it can be shared with others using SECI models with tacit knowledge and explicit knowledge as the origin of the knowledge to be shared.